Quantitative pretreatment EEG predicts efficacy of ACTH therapy in infantile epileptic spasms syndrome. (December 2022) - Kanai, Sotaro; Oguri, Masayoshi; Okanishi, Tohru; Miyamoto, Yosuke; Maeda, Masanori; Yazaki, Kotaro; Matsuura, Ryuki; Tozawa, Takenori; Sakuma, Satoru; Chiyonobu, Tomohiro; Hamano, Shin-ichiro; Maegaki, Yoshihiro
Highlights: We explored the correlation between adrenocorticotrophic hormone (ACTH) outcomes and pretreatment EEG using quantitative analyses in non-lesional infantile epileptic spasms syndrome (IESS). The power and functional connectivity in the lower frequency bands positively correlated with unfavorable seizure outcome. This study may provide novel electrophysiological factors to predict the efficacy of ACTH therapy in non-lesional IESS. Abstract: Objective: This study aimed to determine the correlation between outcomes following adrenocorticotrophic hormone (ACTH) therapy and measurements of relative power spectrum (rPS), weighted phase lag index (wPLI), and graph theoretical analysis on pretreatment electroencephalography (EEG) in infants with non-lesional infantile epileptic spasms syndrome (IESS). Methods: Twenty-eight patients with non-lesional IESS were enrolled. Outcomes were classified based on seizure recurrence following ACTH therapy: seizure-free (F, n = 21) and seizure-recurrence (R, n = 7) groups. The rPS, wPLI, clustering coefficient, and betweenness centrality were calculated on pretreatment EEG and were statistically analyzed to determine the correlation with outcomes following ACTH therapy. Results: The rPS value was significantly higher in the delta frequency band in group R than in group F ( p < 0.001). The wPLI values were significantly higher in the delta, theta, and alpha frequency bands in group R than in group F ( p = 0.007, <0.001, and <0.001, respectively). The clustering coefficient in the delta frequency band was significantly lower in group R than in group F ( p < 0.001). Conclusions: Our findings demonstrate the significant differences in power and functional connectivity between outcome groups. Significance: This study may contribute to an early prediction of ACTH therapy outcomes and thus help in the development of appropriate treatment strategies.